Religious lexis in the Polish-Latin-Latvian dictionary by Jan Kurmin - Szamryk, Konrad Kazimierz (Papers in Linguistics, 2020)
This article presents a quantitative and qualitative analysis of religious vocabulary in Słownik polsko-łacińsko-łotewski [The Polish-Latin-Latvian Dictionary] by Jan Kurmin (ed. Vilnius, 1858). The number of excerpted lexical items (591 units found in 523 entries) has been compared with number of such lexemes excerpted from Polish dictionaries in 20th and 21st century. The comparison shows that the religious lexis in Kurmin’s work even though elaborated remains within the upper limits of religious words found in other dictionaries. Then a lexicological analysis of excerpted lexis is presented: words are grouped it in several semantic fields: faith, religion, congregation, ritual. The author also shows how many lexemes may be regarded as Christian, universal, and non-Christian underlying that those referring to Judaism or pagan beliefs constitute a separate part what results from the specific cultural and sociological trait of the work in question.